Remember love eaudiobook - Balogh, Mary (Ravenswood, 2022)
The beloved queen of Regency romance is back with a brand-new story perfect for fans of Bridgerton. The handsome and charismatic Earl of Stratton, Caleb Ware, has been exposed to the ton for his clandestine affairs—by his own son. As a child, Devlin Ware thought his family stood for all that was right and good in the world. They were kind, gracious, and shared the beauty of Ravenswood, their grand estate, by hosting lavish parties for the entire countryside. But at twentytwo he discovered his whole world was an elaborate illusion, and when Devlin publicly called his family to account for it, he was exiled as a traitor. So be it. He enlisted in the fight against Napoleon and didn't look back for six years. But now his father is dead, the Ware family is broken, and as the heir he is being called home. It's only when Gwyneth Rhys—the woman he loved and then lost after his family banished him—holds out her hand to help him that he is able make the difficult journey and try to piece together his fractured family. It is Gwyneth's loyalty, patience, and love that he needs. But is Devlin's warhardened heart even capable of offering her love in return?